"Knowing That You're Not the Only One": Perspectives on Group-Based Cognitive-Behavioral Therapy for Adherence and Depression (CBT-AD) in Adults With Type 1 Diabetes. Issue 3 (August 2015) - Esbitt, Sabrina A.; Batchelder, Abigail W.; Tanenbaum, Molly L.; Shreck, Erica; Gonzalez, Jeffrey S.
Abstract Depression and illness-specific distress are more common among adults with Type 1 diabetes (T1DM) than the general population and have been associated with poorer control of blood glucose and increased risk for serious diabetes-related complications. Treatment nonadherence has also been associated with depressive symptoms and diabetes-related distress, and has repeatedly been suggested as an important modifiable behavioral pathway linking depression and diabetes outcomes. The present study reports on the feasibility and acceptability of a pilot intervention using group-based cognitive-behavioral therapy to improve treatment adherence among adults with T1DM and elevated levels of diabetes-related distress or depressive symptoms. We describe the components of the intervention and utilize qualitative data along with descriptive outcome data. Our findings suggest that participation in the group was acceptable and associated with reductions in depressive symptoms and diabetes-specific distress. Challenges to feasibility and future directions are discussed.